(untitled) (Texas Journal of Medical Science, 2022)
The COVID-19 virus infection, which has been classified as a pandemic by WHO, is caused by a representative of the group of coronaviruses, which, in turn, belong to the family of seasonal SARS. The SARS-CoV-2 disease, dubbed COVID-19, was officially declared a pandemic by the World Health Organization on March 11, 2020. SARS-CoV-2 contains a single-stranded positive-sense RNA genome surrounded by an extracellular membrane containing a series of crown-like spike glycoproteins. An increase in the number of acute lung abscesses, pleural empyema, high disability and mortality necessitate the search for new methods of diagnosis and treatment. Despite advances in the treatment of pulmonary destruction, mortality remains high, and in complicated forms there is a high percentage of deaths. Therefore, the search for new approaches to the diagnosis and treatment of pyoinflammatory lung diseases is relevant today